The Prešov Evangelical College, the Centre for Education and Science of the Hungarian Evangelical Church - KÓNYA, Péter (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The Evangelical A. V. College in Prešov has been one of the most important Protestant educational institutions in the Kingdom of Hungary since its inception. At the time of its establishment, in the second half of the 17th century, it was not only the first and for a long time the only evangelical a. v. university in the country but also an important political institution, shaping a whole generation of personalities of the social and cultural life of Upper and Lower Hungary. Also for this reason, the activity of the college was temporarily stopped by the state power after several decades, and its planned transformation into a university could not take place. Although in the following century, during the non-violent re-Catholicization, its status temporarily dropped to the level of a secondary school, during the period of tolerance, after 1781, it quickly achieved the status of one of the most important evangelical educational institutions and the title of district college. In the first half of the 19th century, it already had two high-quality university courses, thanks to which it joined a group of universities, academies, making up a special form of the lowest level of university education in Hungarian conditions and a kind of institutional transition to a university. Even though its implementation was again prevented by stormy regional events, the college continued to be an important stand of education and research.